Tradition Changes in the Khataman al-Qur'an in Kediri Region - Retpitasari, Ellyda; Muna, Naila (Proceedings of International Conference on Da'wa and Communication, 2021)
The Covid-19 pandemic spreading in Indonesia has changed all aspects of social life. One of them is in the aspect of changing the culture of the Khataman al-Qur’an tradition in the Kediri Region. This study aims to describe the change in the Khataman al-Qur’an tradition in the Kediri Region. The research method used is the type of qualitative research with a phenomenological approach, while the analytical knife uses the theory of technological determinism. The results of the study state that changes in the implementation of Khataman al-Qur’an through WhatsApp Groups have positive and negative impacts. The positive impact is that it is easy to communicate for worship and maintain consistent motivation in reading the Qur'an. While the negative impact in the aspect of social solidarity such as the lack of emotional bonds and non-verbal cues between fellow members in the group. It is different from the dynamics of the implementation of the Khataman al-Qur’an which was previously held at a certain moment, but for now, it can be held at any time and become a daily habit of the community. In addition, there was a change in the implementation which was initially carried out with the custom of gatherings, and banquets serving food, while the presence of a pandemic changed the implementation of Khataman al-Qur’an through WhatsApp Groups.